Grab and passive sampling applied to pesticide analysis in the São Lourenço river headwater in Campo Verde – MT, Brazil. Issue 4 (3rd April 2018) - Berton, André; Brugnera, Michelle F.; Dores, Eliana F. G. C.
ABSTRACT: In this study, the quality of surface water in the headwaters of São Lourenço River in Mato Grosso, Brazil, was evaluated in relation to contamination by pesticides. For this purpose, samples were collected between December 2015 and June 2016 by grab sampling and by passive sampling using an integrative polar organic compound sampler installed in the field during four 14-day cycles between March and June 2016. The analyses were performed by gas chromatography (CG/MS) and by liquid chromatography (UPLC-MS/MS). The results showed the detection of two pesticides (atrazine and pyraclostrobin) of the five analyzed by passive sampling and eight active principles among the 20 analyzed (malathion, diuron, carbofuran, carbendazim, trifluralin, imidacloprid, metolachlor, and acetamiprid) by grab sampling. The detection of 10 pesticides, even almost a decade after the beginning of a recovery process of the ciliary forest, confirms the headwaters' vulnerability to these contaminants and passive sampling proved to be an important tool in capturing small concentrations of pesticides constituting an interesting complement to grab sampling.